Tin crafts over 20 creative projects for the home - Maguire, Mary (Lovenz Books, 1999)
Working in conjunction with the popular Inspirations magazine, this series of design books presents a fresh look at popular and traditional crafts. A techniques section takes the reader through the essentials of the featured craft.